The Teaching Techniques Used in Teaching Speaking to Young learners on English Massive Program Kediri - Abdullah Achmad Madjid; Entusiastik NA (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2021)
Learning language at an early age has several benefits. However, young leaners attending formal schools in Indonesia get little chance to speak in the classroom. In this case, non-formal education plays a role in helping young learners. English Massive Program is non-formal education given for free by the government of Kediri City. This study aimed to describe the teaching techniques used and the differences of the technique used by an experienced tutor and a less experienced tutor. Descriptive qualitative approach was used as the research design. The data were collected by observing teaching learning process, conducting interview with two tutors, and documentation. It was found that the tutors used several techniques to get the students to speak: information gap, game, listen and repeat, question and answer, and read aloud. The difference of the technique: the experienced tutor used game in every meeting during three observations, while the less experienced tutor used game once during three observations. The use of game by the experienced tutor in every meeting during three observations showed that the experienced tutor understood the characteristics of young learners better. The decisions made by the experienced tutor during three observations also suit the characteristics of experienced tutors or teachers. Key word: experienced tutor, novice or less experienced tutor, teaching speaking, teaching technique, young learners